Political Science in Ecuador, 2005-2019. A discipline in search of institutionalization - Edgar Alberto Zamora-Aviles; María Paz Jervis-Pastor (Íconos, 2021)
This article explores the development of political science as an academic discipline in Ecuador between 2005 and 2019. Three main institutionalization- related dimensions are scrutinized: advancement of training at universities, both at the undergraduate and graduate levels; progression of Ecuadorian- originated publications in high-impact indexed scientific journals, (such as those included in SCOPUS, ISI-WoS) and the evolution of the local academic community. Primary data was obtained from a documentary revision of official higher education reports. Additionally, a bibliometric analysis of scientific publications was performed in the above indexed journals. Finally, a set of interviews was made with members of the local academic community. As a result, it seems possible to claim that after the last 15 years, political science in Ecuador is in the midst of a budding institutionalization process. To a large extent this gradual strengthening is the result of a larger availability of academic programs, both at the undergraduate and graduate levels and of the enhanced relevancy and coherence of the discipline and its output. However, a further consolidation of political science as an academic discipline in Ecuador is hindered by the persistent confusion between so-called “political studies” and “political science proper” and by the lingering prevalence of an identification between the two. This is also related to the unclear social and professional status political scientist enjoy in Ecuadorian society. Many questions remain unsettled regarding the full scope of the discipline’s institutionalization. Also, a thoughtful assessment of this analytical category still remains to be undertaken. Legitimate queries can be made, for instance, about what is the meaning of “politics” as such in Ecuadorian political science.